LOCAL WISDOM IN COFFEE CAFÉ IN MEDAN: ANTHROPOLINGUISTIC APPROACH - Hidayati Hidayati; Arifuddin Arifuddin; Aflina Aflina; Zainab MZ (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
The tradition of drinking coffee, as a cultural heritage of Indonesia, has existed for generations in the city of Medan, the capital of the province of North Sumatra and Sumatra is also a coffee-producing region in Indonesia, so it is not surprising to see the rise of coffee shop business with the current name of coffee café in Medan. Drinking coffee at the café is not just a necessity, it has become a lifestyle and is not limited to age, profession or social status; all the people gather and unite in this place and produce a togetherness. By means of  Anthropolinguistic approach, the one referring  to the study of humans and cultures related to linguistic functions and all the dynamics inherent in human activities, the  research, aimed at revealing local wisdom in coffee cafes in the city of Medan, and based on the notion of cultural heritage preservation, is conducted  using descriptive qualitative methods, revealing a series of community activities related to coffee café in Medan, supported by validity data in the form of interviews and questionnaires, with the key instruments, respondents, who truly understand the phenomenon of the tradition of drinking coffee. The results show that local wisdom is found in the coffee café in Medan, with a percentage of 96, having three points of discussion: Social Interaction Establishment through Polite Language (88%), Cultural Heritage Preservation (96%) and Economic Growth Improvement (92%).